Incidence of Presence & Variation in Anatomical Position of Isthmus of Thyroid Gland in Bangladeshi Cadaver (Bangladesh Journal of Anatomy, 2011)
Context: The thyroid gland is the first endocrine organ to evolve in the vertebrates. It has right and left lobes and connected by narrow median isthmus which lies over the second, third and fourth tracheal rings. A conical pyramidal lobe often ascends towards the hyoid bone from isthmus or the adjacent part of either lobe. It measures about 1.25 cm transversely and vertically. Its size and site vary greatly. Isthmus is topographically related with some important anatomical structures. So this study was carried out to determine the incidence of presence & variation in anatomical position of isthmus of thyroid gland of Bangladeshi people of different age groups to establish a normal standard. Study type: Descriptive cross-sectional study. Place and period of study: Department of Anatomy, Mymensingh Medical College. from October’2004 to February’2005. Materials: The study was carried out on 60 cadavers of different age groups age ranging from 11 to 70 years. Thyroid glands were collected from unclaimed dead bodies autopsied in Forensic Medicine Department of Mymensingh Medical College. Methods: The collected specimens were divided into age group A (upto 18 years), group B (18 to 45 years), group C (above45 years). All specimens were examined morphologically by fine dissection method. Result: In the present study isthmus was present in 41 (68.33%) cases. In those thyroids which were devoid of isthmus, lobes were found to be merged with each other in the midline but in one case two lobes were found completely separated from each other. It was evident that the posterior relations of isthmus were widely variable. In only 18% cases it was found at its usual position- against the 2nd, 3rd and 4th tracheal rings. In the present study more frequent location of isthmus was found at 1st, 2nd, 3rd and 2nd, 3rd, 4th tracheal rings. In both cases their incidences were 18.3%. Conclusion: The present study will help to increase the information pool on the anatomy of thyroid gland of Bangladeshi people. To establish a normal standard for Bangladeshi people, further studies with large samples from different zones of the country are suggested. Key Word- Isthmus; Human Thyroid gland; Incidence; Posterior relation; Bangladesh DOI: http://dx.doi.org/ 10.3329/bja.v9i1.8144 Bangladesh Journal of Anatomy January 2011, Vol. 9 No. 1 pp 26-29